(untitled) (Global Journal of Human-Social Science, 2013)
Intraference is used in this paper as a more economical for Selinker s overgeneralization of linguistic materials and semantic features Richards and Sampson s intralingual interference and Labov s internal principle of linguistic change Library research questionnaires and the record of live linguistic events by educated Nigerians were used to gather data from 2004 to 2013 with a view to establishing morphemic intraference variations between ENEm and SBE It was found that educated Nigerians overstretch plurality rule redeploy affixes clip and blend to fabricate lexical items that may not be found in SBE and standard dictionaries These morphological features which are not necessarily vulgar errors of ignorance but the outcomes of creativity and level of competence engendered by some psycho-sociolinguistic dynamics distinguish ENE from SBE and American English